Captain Fantastic - Ross, Matt; Mortensen, Viggo, 1958-; Langella, Frank; MacKay, George, 1992-; Somers, Alex (Universal City, CA : Universal Studios Home Entertainment, 2016)
After the death of his wife, a man raising six children off the grid learns that he must find a way to integrate his family back into society.
Originally released as a motion picture in 2016.
Dolby digital 5.1, wide screen 2.40:1.
Features: Insane or insanely great?
Camera, Stephane Fontaine ; production design, Russell Barnes ; editor, Joseph Krings ; music, Alex Somers.
Viggo Mortensen, Frank Langella, George MacKay, Samantha Isler, Annalise Basso.
MPAA rating: R.
Keywords: Families -- Drama; Parent and child -- Drama; Grief -- Drama; Fiction films; Video recordings for the hearing impaired; Feature films